2017
DOI: 10.23956/ijarcsse/v6i12/01204
|View full text |Cite
|
Sign up to set email alerts
|

Cyber Security Issues in Nigeria and Challenges

Abstract: Cyber-space refers to the boundless space known as the internet. Cyber-security is the body of rules put in place for the protection of the cyber space. Cyber-crime refers to the series of organized crime attacking both cyber space and cyber security. The Internet is one of the fastest-growing areas of technical infrastructure development. Over the past decades, the growth of the internet and its use afforded everyone this opportunity. Google, Wikipedia and Bing to mention a few, give detailed answers to milli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 2 publications
(3 reference statements)
1
11
0
Order By: Relevance
“…Mbanaso and Dandaura (2015) described cyberspace as the merger of internet, information systems and people. In addition, cyberspace was conceived as the boundless space known as the internet (Makeri, 2017).…”
Section: The Concept Of Cyberspacementioning
confidence: 99%
See 2 more Smart Citations
“…Mbanaso and Dandaura (2015) described cyberspace as the merger of internet, information systems and people. In addition, cyberspace was conceived as the boundless space known as the internet (Makeri, 2017).…”
Section: The Concept Of Cyberspacementioning
confidence: 99%
“…It is geared towards ensuring the safety and protection of users against security risks in the cyber arena. Makeri (2017) observed that as we become more dependent on cyberspace we undoubtedly face new risks. The security architecture of many countries including Nigeria was badly challenged by COVID-19 pandemic (Osah & Adewumi, 2020).…”
Section: Porous Cyberspacementioning
confidence: 99%
See 1 more Smart Citation
“…Real transformation involves exploring new ways of doing business, while increasing efficiency, costs reduction and higher investment returns. While navigating these new frontiers cautiously, we should remain aware that digital networking, data specifications and distributions, which enhance a more digitalized means of livelihood, have equally become more abstract, which may, in turn, increase our vulnerability to internet risks [3]. Increasingly, our infrastructures are also frequently becoming complex and relying on external dependencies.…”
Section: Introductionmentioning
confidence: 99%
“…Cybercrime is one of the most complex, widespread, and persistent social problems ravaging the cyberspace, and Africa is not immune from the ensuing treachery because of her weak legal and regulatory cyber policies (Abdul-Rasheed Ishowo et al, 2016; Ajah & Onyejegbu, 2019; Jaishankar, 2010; Ndubueze et al, 2013; Odo & Odo, 2015; Quarshie & Martin-Odoom, 2012). The cyberspace is driving business innovations and growth globally, and at the same time, exposing corporate organizations to new and emerging internet-assisted crimes (Longe et al, 2009; Makeri, 2017; Quarshie & Martin-Odoom, 2012). Today, the negative frontiers of the cyberspace that corporate organizations are contending with include: hacking, malware attacks, cyber-terrorism, spoofing, phishing, spam, virus attacks, child pornography, cyber vandalism, cyberstalking, data modification, email bombing, and cybersquatting (Fanawopo, 2004).…”
Section: Introductionmentioning
confidence: 99%